Immune response to SARS-CoV-2 mRNA vaccination and booster dose in patients with multiple myeloma and monoclonal gammopathies: impact of Omicron variant on the humoral response. (31st December 2022) - Storti, Paola; Marchica, Valentina; Vescovini, Rosanna; Franceschi, Valentina; Russo, Luca; Notarfranchi, Laura; Raimondi, Vincenzo; Toscani, Denise; Burroughs Garcia, Jessica; Costa, Federica; Dalla Palma, Benedetta; Iannozzi, Nicolas Thomas; et al.
ABSTRACT: The humoral and cellular response to SARS-CoV-2 mRNA full vaccination and booster dose as well as the impact of the spike variants, including Omicron, are still unclear in patients with multiple myeloma (MM) and those with pre-malignant monoclonal gammopathies. In this study, involving 40 patients, we found that MM patients with relapsed-refractory disease (MMR) had reduced spike-specific antibody levels and neutralizing titers after SARS-CoV-2 vaccination. The five analyzed variants, remarkably Omicron, had a significant negative impact on the neutralizing ability of the vaccine-induced antibodies in all patients with MM and smoldering MM. Moreover, lower spike-specific IL-2-producing CD4 + T cells and reduced cytotoxic spike-specific IFN-γ and TNF-α-producing CD8 + T cells were found in MM patients as compared to patients with monoclonal gammopathy of undetermined significance. We found that a heterologous booster immunization improved SARS-CoV-2 spike humoral and cellular responses in newly diagnosed MM (MMD) patients and in most, but not all, MMR patients. After the booster dose, a significant increase of the neutralizing antibody titers against almost all the analyzed variants was achieved in MMD. However, in MMR patients, Omicron retained a negative impact on neutralizing ability, suggesting further approaches to potentiating the effectiveness of SARS-CoV-2 vaccination in these patients.